A core outcome set for vasomotor symptoms associated with menopause: the COMMA (Core Outcomes in Menopause) global initiative. Issue 8 (August 2021) - Lensen, Sarah; Archer, David; Bell, Robin J.; Carpenter, Janet S.; Christmas, Monica; Davis, Susan R.; Giblin, Karen; Goldstein, Steven R.; Hillard, Tim; Hunter, Myra S.; Iliodromiti, Stamatina; Jaisamrarn, Unnop; et al.
Abstract: Objective: Vasomotor symptoms (VMS) (hot flashes and night sweats) affect most women over the menopause transition. Comparing the safety and effectiveness of treatments for vasomotor symptoms is limited by the use of inconsistent outcome measures, and uncertainty as to which outcomes are most important to symptomatic women. To address this, we have developed a Core Outcome Set (COS) for use in clinical trials of treatments for VMS. Methods: We systematically reviewed the primary outcomes measured in randomized controlled trials of treatments for VMS. These were refined and entered into a two-round modified Delphi survey completed by clinicians, researchers, and postmenopausal women between November 2019 and March 2020. Outcomes were scored on a nine-point scale from "not important" to "critically important." Two international consensus meetings were held to finalize the COS. Results: Based on the systematic review, 13 separate outcomes were included in the Delphi process. This was completed by 227 participants of whom 58% were postmenopausal women, 34% clinicians, and 8% researchers. Predefined thresholds were applied to categorize importance scores obtained during Round 2 of the Delphi survey. These informed discussions at the consensus meetings which were attended by 56 participants from 28 countries. The final COS includes six outcomes: 1) frequency of VMS, 2) severity of VMS, 3) distress, bother or interference caused by VMS, 4) impact on sleep, 5) satisfaction with treatment, and 6) side-effects of treatment. Conclusion: Implementation of this COS will: better enable research studies to accurately reflect the joint priorities of postmenopausal women, clinicians and researchers, standardize outcome reporting, and facilitate combining and comparing results from different studies, and ultimately improve outcomes for women with bothersome VMS. N/A: Video Summary: http://links.lww.com/MENO/A763 . Abstract : Supplemental Digital Content is available in the text